Peran Guru Dalam Menangani Siswa Yang Kurang Disiplin Beribadah Di MTS Swasta Mamiyai Al-Ittihadiyah - Aliyah Putri; Dedi Masri; Mohammad Al Farabi (CV. ITTC INDONESIA, 2025)
Abstract: The role of teachers in shaping student character is very important, especially in the aspect of discipline in worship. This article discusses the strategies and roles of teachers in dealing with students who lack discipline in practicing worship in the school environment. Through pedagogical approaches, exemplary behavior, and religious values-based coaching, teachers can be the main motivators in increasing students’ awareness of worship. In addition, the use of personal approach methods, strengthening the religious environment, and cooperation with parents and school parties are supporting factors in forming disciplined worship habits. This study uses a qualitative method with a descriptive approach to analyze the role of teachers based on experience and observation in the school environment. The results showed that the teacher’s role as a mentor, motivator, and role model has a significant influence in improving students’ worship discipline. Therefore, sustainable efforts in building a culture of worship discipline need to be supported by various parties in order to create a generation that is religious and has character. Keywords: Teacher’s Role, Discipline of Worship